Ear Parade: A Call for Preventive Actions to Strengthen the Healthcare System against Hearing Loss - Lopes, Paula Tardim; Bento, Ricardo Ferreira (International Archives of Otorhinolaryngology, 2020)
Introduction Approximately 10 million people in Brazil have some hearing impairment. Because of the natural progression of hearing impairment to presbycusis, coupled with the increasing number of young people exposed to the risk factors for early hearing loss, the social impact of hearing impairment is high.Objective A team of otolaryngologists and speech therapists conducted an unprecedented worldwide campaign in the primary health sector, aiming to reduce the global burden of hearing impairment with preventive measures.Methods A cultural information campaign called “Ear Parade” was developed. It lasted 3 months, during which São Paulo received information on the prevention of deafness and the importance of hearing rehabilitation to reduce prejudice against the use of hearing aids.Results The information was relayed through an art exhibition of public paintings, including 62 sculptures of ears, 2.40 meters high, which colored the city, elucidating the beauty of hearing. The media coverage impacted 170 million people, and at the end of the campaign, a nongovernmental organization was established to raise resources for hearing rehabilitation. In addition, an auction of the ear sculptures raised money toward hearing aid batteries and stem-cell research for hearing.Conclusion The present paper presents the effects of this campaign. Information dissemination is a powerful preventive measure for the primary healthcare system to reduce future treatment expenditures.
Keywords: deafness; hearing loss; prevention; healthcare; dementia; prejudice